Dietary methionine restriction alleviates oxidative stress and inflammatory responses in lipopolysaccharide-challenged broilers at early age - Pang, Xiyuan; Miao, Zhiqiang; Dong, Yuanyang; Cheng, Huiyu; Xin, Xiangqi; Wu, Yuan; Han, Miaomiao; Su, Yuan; Yuan, Jianmin; Shao, Yuxin; Yan, Lei; Li, Jianhui (Frontiers in Pharmacology, 2023)
In this study, we investigated the effect of dietary methionine restriction (MR) on the antioxidant function and inflammatory responses in lipopolysaccharide (LPS)-challenged broilers reared at high stocking density. A total of 504 one-day-old male Arbor Acre broiler chickens were randomly divided into four treatments: 1) CON group, broilers fed a basal diet; 2) LPS group, LPS-challenged broilers fed a basal diet; 3) MR1 group, LPS-challenged broilers fed a methionine-restricted diet (0.3% methionine); and 4) MR2 group, LPS-challenged broilers fed a methionine-restricted diet (0.4% methionine). The results showed that: LPS increased the liver histopathological score significantly (P < 0.05); LPS significantly decreased serum total antioxidant capacity (T-AOC), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) activity at 3 h after injection (P < 0.05); the LPS group had a higher content of Interleukin‐ 1 (IL‐1β), Interleukin‐6 (IL‐6), and tumor necrosis factor‐α (TNF‐α), but a lower content of Interleukin‐10 (IL‐10) than the CON group in serum (P < 0.05). Compared with the LPS group, the MR1 diet increased CAT, SOD, and T-AOC, and the MR2 diet increased SOD and T-AOC at 3 h after injection in serum(P < 0.05). Only MR2 group displayed a significantly decreased liver histopathological score (P < 0.05) at 3 h, while it was did both the MR1 and MR2 groups at 8 h. Both MR diets significantly decreased LPS, CORT, IL‐1β, IL‐6, and TNF‐α content, but increased IL‐10 content in serum (P < 0.05). Moreover, the MR1 group displayed significantly increased expression of nuclear factor erythroid 2-related factor 2 (Nrf2), CAT, and GSH-Px at 3 h; the MR2 group had a higher expression of Kelch-like ECH-associated protein 1 (Keap1), SOD, and GSH-Px at 8 h (P < 0.05). In summary, methionine restriction can improve antioxidant capacity, immunological stress, and liver health in broilers challenged with LPS. The MR groups experienced similar effects on relieving stress, but MR1 alleviated oxidative stress more rapidly. It is suggested that precise regulation of methionine levels in poultry with stress may improve the immunity of broilers, reduce feed production costs, and increase production efficiency in the poultry industry.